Perceived caring attributes and priorities of preregistration nursing students throughout a nursing curriculum underpinned by person‐centredness. Issue 13 (27th May 2018) - Cook, Neal F.; McCance, Tanya; McCormack, Brendan; Barr, Owen; Slater, Paul
Abstract : Aim and objective: To explore preregistration nursing students' caring attributes development through a person‐centred focused curriculum. Background: Developing caring attributes in student nurses to the point of registration has historically been challenging. Globally, curricula have not yet demonstrated the ability to sustain and develop caring attributes in this population, despite its centrality to practice. Design and methods: This longitudinal cohort study tracked how University preregistration nursing students ( N  = 212) developed their caring attributes over the 3 years of their programme using repeated measures at the end of each year with the same cohort. The Caring Dimensions Inventory (35 item version with 25 caring items under three constructs (technical, intimacy and supporting) and 10 inappropriate or unnecessary construct items) was used and data analysed using Mokken scale analysis to create a hierarchy of actions that students deemed as caring. Repeated measures of analysis of variance enabled evaluation of changes in responses over time. Results: Students developed their caring attributes throughout their programme, ranking 22 of 25 items as caring (with statistical significance) at the end of year 1, 18 at the end of year 2 and all 25 caring items at the end of their final year. No unnecessary or inappropriate construct items were ranked as caring at any data collection point. Participants consistently ranked assisting a person with an activity of living, listening to a patient and involving them in their care as the most caring actions. Conclusion: This study found caring attributes can not only be sustained, but can also be developed throughout a preregistration nursing education programme grounded in person‐centredness. Relevance to clinical practice: Internationally, caring attributes are challenging to develop and sustain throughout preregistration education, largely being diminished over time. Little published evidence evidences how person‐centred frameworks are successfully integrated into preregistration nursing curricula to develop person‐centred nurses.